2007
DOI: 10.1056/nejmoa071880
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Ventricular Pacing to Reduce Atrial Fibrillation in Sinus-Node Disease

Abstract: Dual-chamber minimal ventricular pacing, as compared with conventional dual-chamber pacing, prevents ventricular desynchronization and moderately reduces the risk of persistent atrial fibrillation in patients with sinus-node disease. (ClinicalTrials.gov number, NCT00284830 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
197
1
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(246 citation statements)
references
References 34 publications
13
197
1
19
Order By: Relevance
“…29,30 As a consequence, this should result in a more frequent choice of dual-chamber pacemakers in females, due to the demonstrated harmful effect of ventricular pacing on the outcome of sinus node dysfunction. 31,32 Surprisingly, in the 'real-world', females receive single-chamber devices more frequently. In an analysis on 36,312 elderly Medicare beneficiaries undergoing pacemaker implantation, Lamas et al showed that male gender was an independent predictor of a dual-chamber pacemaker implantation, 33 thus supporting a sex-bias in pacemaker implantation procedures.…”
Section: Permanent Pacemakersmentioning
confidence: 99%
“…29,30 As a consequence, this should result in a more frequent choice of dual-chamber pacemakers in females, due to the demonstrated harmful effect of ventricular pacing on the outcome of sinus node dysfunction. 31,32 Surprisingly, in the 'real-world', females receive single-chamber devices more frequently. In an analysis on 36,312 elderly Medicare beneficiaries undergoing pacemaker implantation, Lamas et al showed that male gender was an independent predictor of a dual-chamber pacemaker implantation, 33 thus supporting a sex-bias in pacemaker implantation procedures.…”
Section: Permanent Pacemakersmentioning
confidence: 99%
“…This type of pacing causes an abnormal left ventricular electricalactivation sequence with an electromechanical delay in contraction (right to left ventricle dyssynchrony) and, subsequently, increased mitral regurgitation and decreased EF (17)(18)(19)(20). Several preventive pacing algorithms have been developed to reduce the percentage of right ventricular pacing but these might be used only in patients with sinus node dysfunction, not in patients with advanced AV block and a high percentage of ventricular pacing (21,22). In elderly patients with underlying risk factors for heart failure (diastolic dysfunction and comorbidities), more than 50% of RV apical pacing may trigger the complications (23).…”
Section: Discussionmentioning
confidence: 99%
“…Доля право-желудочковой стимуляции составила 9,1 и 99,0% соответ-ственно (р<0,001). Не было выявлено различий в частоте госпитализаций по причине декомпенсации ХСН (p=0,62) и смертности (p=0,54) между группами [19].…”
Section: кардиология и сердечно-сосудистая хирургия 1 2015unclassified